Advances in fuzzy logic and technology 2017 : proceedings of: EUSFLAT-2017 - the 10th conference of the European Society for Fuzzy Logic and Technology, September 11-15, 2017, Warsaw, Poland IWIFSGN'2017 - the sixteenth International Workshop on Intuitionistic Fuzzy Sets and Generalized Nets, September 13-15, 2017, Warsaw, Poland.: proceedings of: EUSFLAT-2017 - the 10th conference of the European Society for Fuzzy Logic and Technology, September 11-15, 2017, Warsaw, Poland IWIFSGN'2017 - the sixteenth International Workshop on Intuitionistic Fuzzy Sets and Generalized Nets, September 13-15, 2017, Warsaw, Poland. Volume 3 ([2018]) - Unknown
No abstract available